CONTEMPORARY DYNAMICS IN LEGAL MANAGEMENT: ADAPTING TO REGULATION AND BUSINESS EXPECTATIONS - Sigit Sugiardi; Ignatius Septo Pramesworo; Bernard Tifaona (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Responsive regulation is key to balancing consumer protection and business innovation in the financial technology sector. Piloting new products under regulatory supervision can be a solution to test new products while maintaining a clear legal framework. Multi-stakeholder consultation processes and dialogue with regulators add to the complexity of rule adaptation. For legal management, a strong regulatory monitoring capacity is required along with a dedicated team to ensure timely compliance. On the other hand, businesses need flexibility through anticipation of rule changes, data analytics, and the latest technology to observe the impact of regulations in real-time. Close multi-stakeholder collaboration is key to creating rules that are fair to all parties and support sustainable innovation. Joint adaptability between government, industry, and academia will enable the growth of the digital economy without abandoning consumer protection.